Peran Kepala Sekolah dalam Peningkatan Mutu Pendidikan di Sekolah Dasar Negeri (Jurnal Arjuna : Publikasi Ilmu Pendidikan, Bahasa dan Matematika, 2025)
Education plays a pivotal role in Indonesia's national development, as it significantly impacts the quality of human resources. Consequently, the government prioritizes education by aiming to develop students who are devoted to God Almighty, knowledgeable, and possess noble character. Educational personnel, particularly school principals, hold a strategic position in achieving these objectives. A school principal's leadership is essential in managing educational resources, collaborating with teachers and staff, and guiding students toward learning goals. In a decentralized education system, principals function as top administrators with multiple roles, including manager, supervisor, educator, leader, innovator, and motivator. However, educational challenges often stem from distortions in meaning and practice, which contribute to declining education quality. As the primary agent of school leadership, the principal must demonstrate professional competence to identify school needs, empower existing resources, and involve the community in achieving educational goals. The concept of modern schools—such as model and exemplary schools—has emerged in response to society’s demand for quality education. In this context, the school principal is required to lead with strategic planning, administrative effectiveness, and inspiring leadership to ensure school success and student achievement. This study explores the multifaceted role of the school principal in improving educational quality, emphasizing their responsibilities in management, leadership, educational support, and administration. It concludes that professional and competent principals are essential for shaping a school environment conducive to educational excellence and preparing competitive human resources in the global era.